Misclassification in Assessment of First Trimester In-utero Exposure to Drugs Used Proximally to Conception: the Example of Letrozole Utilization for Infertility Treatment. Issue 2 (15th October 2018) - Bird, Steven T; Toh, Sengwee; Sahin, Leyla; Andrade, Susan E; Gelperin, Kate; Taylor, Lockwood; Song, Jaejoon; Hampp, Christian
Abstract: Letrozole is an aromatase inhibitor that has an unapproved use for ovulation induction with infertility. Because of the proximity of this use to conception, we selected letrozole to study the effect of 3 different methods for identifying the pregnancy start date and their impact on exposure misclassification. Using electronic health data from the US Sentinel database (2001–2015), we identified live-birth pregnancies conceived through in-vitro fertilization or intrauterine insemination. The pregnancy start was calculated using 1) a validated algorithm to estimate the last menstrual period (LMP), 2) LMP + 14 days (i.e., conception estimate), and 3) the fertility-procedure date. We identified 47, 628 live-births after intrauterine insemination ( n = 24, 962) and in-vitro fertilization ( n = 22, 666), in which 2, 458 (5.3%) mothers received letrozole. The algorithm-based conception estimate occurred within 14 days of the fertility procedure for 78.3% of pregnancies. Defining pregnancy start as LMP (45.7/1, 000 pregnancies) or LMP + 14 days (12.7/1, 000 pregnancies) overestimated letrozole exposure during pregnancy by 8.4-fold and 2.3-fold, respectively, compared with defining it at the date of the fertility procedure (5.5/1, 000 pregnancies). While most studies of drug utilization in pregnancy use LMP as the conventional pregnancy start, this introduced substantial exposure misclassification in the example of letrozole. LMP + 14 days was less biased. Researchers should carefully consider the impact of the method for identifying the pregnancy start date on the potential for exposure misclassification.